The AI doc : or how I became an apocaloptimist [videorecording (Blu-Ray)] - Roher, Daniel; Morello, Jenni; Meyer, Lowell A.; Coombe, Davis; Broadway, Daysha; De Vries, Marius; Robertson, Matt (Focus Features, 2026)
"A father-to-be tries to figure out what is happening with all this AI insanity. The AI Doc: Or How I Became an Apocaloptimist is a hand-made, eye-opening documentary about the most powerful technology humanity has ever created ... and what's at stake if we get it wrong."--Container.